2012
DOI: 10.1111/j.1477-9552.2012.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Investing Today or Tomorrow? An Experimental Approach to Farmers’ Decision Behaviour

Abstract: An understanding of farmers’ decision‐making behaviour is important for adequate forecasts as well as policy recommendations regarding structural changes. We experimentally analyse the investment behaviour of real farmers. The observed investment decisions are contrasted with theoretical benchmarks from classical investment theory and the real options approach. Our results show that both theories cannot exactly explain investment behaviour. However, farmers learn from former investment decisions and do conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
(101 reference statements)
5
18
0
1
Order By: Relevance
“…Nevertheless, the observed disinvestment reluctance is even more pronounced than predicted by the ROA. These findings are consistent with previous investigations (Oprea et al 2009;Sandri et al 2010;Musshoff et al 2013;Maart-Noelck and Musshoff 2013).…”
Section: Test Of H1 'Roa Superiority To Npv'supporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, the observed disinvestment reluctance is even more pronounced than predicted by the ROA. These findings are consistent with previous investigations (Oprea et al 2009;Sandri et al 2010;Musshoff et al 2013;Maart-Noelck and Musshoff 2013).…”
Section: Test Of H1 'Roa Superiority To Npv'supporting
confidence: 94%
“…Their research revealed that participants can learn from personal experience to closely approximate optimal exercise of wait options. Maart-Noelck and Musshoff (2013) carried out an experiment with 106 farmers on the decision behaviour in a (non)-agricultural investment situation. They found that the timing of investments was not exactly predictable with the ROA or with the NPV but lied between both benchmarks.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Petani-peternak bersifat rasional sesuai dengan hasil penelitian Maart-Noelck & Musshoff (2013) yang menyatakan bahwa perilaku petani dalam mengambil keputusan untuk berinvestasi guna memperluas usahanya adalah belajar dari investasi sebelumnya dan melakukan pertimbangan nilai yang diperoleh dengan mengamati dari waktu ke waktu. Jika investasi dari waktu ke waktu dapat memberikan nilai tambah atau menguntungkan, maka petani akan memutuskan berinvestasi sehingga pada gilirannya dapat meningkatkan produksi dan sebaliknya.…”
unclassified
“…This methodology presented by Holt and Laury [36] has not been changed and is already established in agricultural economics [43,44]. First, participants are introduced to the game with the explanation of the lottery whereby participation is completely voluntary and the outcomes are always positive.…”
Section: Holt and Laury Lotterymentioning
confidence: 99%